FDI versus local industrial investment: a human capital perspective of development - El Shamy, Hebatallah Hamdy (AUC Knowledge Fountain, 2010)
This research looks at three automotive components' factories in Egypt, equally benchmarked in all aspects, except for the nationality and nature of their ownership structure and their unique management arrangements and styles. One is totally foreign owned, but co-managed, the second is partly foreign owned, and managed, and the third is totally Egyptian-owned and managed. The study eventually, seeks to uncover the inner workings of the role of FDI vis-Ã -vis that of local industrial intellectual elite (progressive entrepreneurs), in conjunction with the pattern of intermittent reliance on foreign technical assistance. It probes the different ways these three different arrangement settings differ or converge in their agency for human capital accumulation, in the form of technical cultural and social expertise, while levering aspects of leadership and empowerment. â Way- backâ appointed employee samples, in each factory, are tested against their most recently appointed counterparts, for their level of accumulated technical, social and cultural expertise. The research incorporates a varied mix of tools of statistical analysis, where â a single case study with multiple embedded units study' approach, including , theoretical and political-economic contextualization, all combine, in order to give a clearer picture of the situation of industrial modernity versus overall modernity against a contemporary discourse of global modernity.